Pengembangan Acne patch Ekstrak Pegagan (Centella asiatica L. Urban) sebagai Sediaan Anti-Acne - Setia Budi; Tuti Alawiyah; Malisa Ariani (Journal of Pharmaceutical and Sciences, 2026)
Background: Acne vulgaris is a chronic inflammatory skin condition where prolonged use of synthetic antibacterials can lead to bacterial resistance, necessitating natural alternatives. Centella asiatica extract, rich in triterpenoid saponins and flavonoids, exhibits antibacterial activity against acne-causing bacteria. Objective: This study aimed to formulate and evaluate the physical properties and in vitro penetration of an acne patch containing C. asiatica extract using a combination of polyvinylpyrrolidone (PVP) K30 and ethyl cellulose polymers. Methods: The extract was obtained by 96% ethanol maceration and formulated into three patch formulas with varying polymer ratios (PVP K30:ethyl cellulose = 100:300, 200:200, and 300:100 w/w). All patches were prepared using the solvent casting method. Evaluations included organoleptic properties, homogeneity, thickness, folding endurance, moisture content, weight uniformity, and in vitro penetration using a Franz diffusion cell. Results: All formulations produced homogeneous, transparent patches with uniform thickness (approx. 1 mm). However, all formulas exhibited poor mechanical properties, with folding endurance values (<30 folds) far below the required standard (>300 folds). Moisture content (21.7-23.3%) exceeded the recommended limit (<10%), indicating potential instability. Furthermore, the cumulative in vitro penetration of the active compound through rat skin was very low (0.001-0.004 µg/cm²) over 180 minutes. Conclusion: The C. asiatica extract acne patches demonstrated acceptable basic physical characteristics (homogeneity, thickness). However, they require significant optimization to improve mechanical strength, reduce moisture content, and enhance drug penetration before being considered a viable anti-acne preparation.